Republican Principles in International Law - Sellers, M. author. aut Link
X, 266 p.
Keywords: Republican Principles in International Law considers the fundamental requirements of a just world order, as applied to public international law. This book sets the standard for legitimate government, both within and beyond the jurisdiction of separate states and nations.